Evaluation of the pollution levels of landfill sites – the Landfill Pollution Index (LPI) - Theng, Lee Chong; Mohd Nasir Hassan; Muhamad Awang; Mohd Yazid Saman (Environmental Management Society, Malaysia, 2004)
Most of the solid waste disposal sites in Malaysia are either open dumps or controlled tipping. The pollution levels from these sites are expected to be high especially the contamination of soil, air, surface and underground water. All these pollutions have direct and indirect links to human being. The risks associated with solid waste disposal sites involved three compartments or media, i.e. the atmosphere, water and soil. This ‘Cross media’ or ‘Multimedia’ impacts phenomenon has been recognized in various countries as being of potential importance and complicated. This study discusses the development of a new and simple evaluation system to assess the pollution levels of landfill sites. The Landfill Pollution Index (LPI) was introduced, which incorporated with 4 other sub-indices, i.e. the Environmental Degradation Index (EDI) for water quality, gas emission, chemicals in surface water and chemicals in groundwater. Active and closed landfill sites in Kuala Lumpur were assessed by using the LPI approach. The results show that Taman Beringin was the most polluted landfill with the LPI of 719.56, followed by Jinjang Utara (383.51), Paka 1 (197.66), Brickfields (128.90), Paka 2 (113.72), Sri Petaling (30.81) and Sungei Besi (17.87). For detailed evaluation, the LPI calculated and was further elaborated by using the sub-indices, i.e. the EDI. The results provide information on the extent of pollution at each particular landfill site in terms of different components such as water quality, gas emission, soil and groundwater. This helps the landfill operators as well as decision makers in giving priority to remedial or rehabilitate the environmental conditions of the landfill sites. In summary, a new evaluation system had been introduced in this study in order to produce simple and reliable tool to evaluate or assess the pollution levels for municipal waste landfill sites. Based on the assessment of Kuala Lumpur landfill sites, it can be concluded that the risk and pollution levels of landfill sites in Kuala Lumpur area are relatively high, but it is site-specific and varies from one landfill site to another